Tainted milk : breastmilk, feminisms, and the politics of environmental degradation - Boswell-Penc, Maia, 1964- (Albany : State University of New York Press, 2006)
"Tainted Milk provides an in-depth analysis of the debate about infant nourishment issues, with a particular focus on environmentally contaminated breastmilk. Maia Boswell-Penc asks why feminists and environmentalists have, for the most part, remained relatively quiet about the fact that environmental toxins have been appearing in breastmilk. She argues that feminists avoid the topic because of their fear of focusing on biological mothering and essentialist thinking, while environmentalists are reluctant to be perceived as fearmongers advocating formula use and contributing to public hysteria. Boswell-Penc also points to the continuing racism, classism, ageism, and corporatization that leaves the less privileged among us more vulnerable."--Jacket
Machine generated contents note: Ch. 1 evolving narrative of infant food contamination : historical vignettes -- Ch. 2 Toxic disclosure : the growing awareness of environmentally contaminated breastmilk in the context of much-needed breastfeeding advocacy -- Ch. 3 Breast fetishization, breast cancer, and breast augmentation : the curious omissions of breastfeeding and breastmilk contamination as significant feminist issues -- Ch. 4 Polluting the "waters" of the most vulnerable : environmental racism, environmental justice, and breastmilk contamination.
Includes bibliographical references (pages 189-207) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Breastfeeding -- Health aspects -- United States -- History; Breast milk -- Contamination -- United States -- History; Infants -- Nutrition -- United States -- History; Food contamination -- Environmental aspects; Environmental degradation -- Health aspects; Pollution -- Health aspects; Infants; Milk, Human -- chemistry; Breast Feeding -- adverse effects; Environmental Pollutants -- adverse effects; Food Contamination; Infant; United States; Lait maternel -- Contamination -- États-Unis -- Histoire; Aliments -- Contamination -- Aspect de l'environnement.; Nourrissons; infants; SCIENCE -- Environmental Science (see also Chemistry -- Environmental); POLITICAL SCIENCE -- Public Policy -- Environmental Policy; Infants; Breast milk -- Contamination; Breastfeeding -- Health aspects; Environmental degradation -- Health aspects; Food contamination -- Environmental aspects; Infants -- Nutrition; Pollution -- Health aspects; United States; History